Upaya Pasangan Suami Istri Disabilitas dalam Membangun Keluarga Sakinah di Kecamatan Buduran Kabupaten Sidoarjo - Aisa, Siti; Islam Z.E, Muhammad Rasikhul (Madani: Jurnal Ilmiah Multidisiplin, 2024)
In Islam, a happy family is called a family that is peaceful, loving, and compassionate. However, how is it in a family inhabited by a husband and wife with disabilities? Of course it will be different and it can be said that it is difficult to achieve a harmonious family. This type of research is descriptive qualitative, the methods used in this study are interviews, observations, and documentation. The subjects studied were a husband and wife with disabilities who lived in Buduran District, Sidoarjo Regency. Based on the results of the research conducted, it can be concluded that: (1) The understanding of a husband and wife about a harmonious family is: a sense of understanding, mutual acceptance of the partner's condition, tantra and strong in facing every problem that exists, that is what is understood by a husband and wife with disabilities about the meaning of a harmonious family. (2) The efforts of a husband and wife with disabilities in forming a harmonious family are: Willingness in the family to accept the partner's condition is very much needed. They need personal abilities that have existed since childhood. But that does not discourage this family from continuing to earn a living to meet the needs of their family members even in less than normal circumstances. Creating a sense of comfort and peace in the family is a need that must be achieved. (3) Obstacles in the household of people with disabilities, both economic problems, lack of knowledge, and physical disabilities in family members. To deal with this, people with disabilities must be more patient and resigned to accepting the trials in life and remain enthusiastic in trying to pursue their ideals in household life.